Humidity sensing characteristics of Sn doped Zinc oxide based quartz crystal microbalance sensors - Hendi, A. A.; Alorainy, R. H.; Yakuphanoğlu, Fahrettin (Springer, 2014)
The electrical, optical and humidity sensor properties of nanostructured ZnO samples were investigated. The structural properties of Sn doped ZnO samples were characterized by X-ray diffraction and atomic force microscopy. It was found that the all samples have a hexagonal crystal structure. The electrical conductivity of the samples indicates that undoped and Sn doped ZnO samples exhibit the semiconducting behavior. The optical absorption method was used to determine the optical band gaps of the samples. The optical band gap and activation energy values of the ZnO samples were changed with Sn doping. The ZnO based on quartz crystal microbalance humidity sensors were prepared and sensing properties of the sensors were changed with Sn doping. The response time required to reach 70 % is about 13-16 s, while the recovery time from 70 to 30 % RH is about 13-15 s. The fast response of the sensors is due to easy diffusion of water molecules between ZnO nanopowders. The prepared sensors have a high reproducibility and sensitivity for humidity sensing applications.
Keywords: Metal oxide semiconductor; Quartz crystal microbalance humidity sensor; Sol-gel method